1997
DOI: 10.1093/jjco/27.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Features and Survival in Patients With Hepatitis B and C Virus-Related Hepatocellular Carcinoma

Abstract: We analyzed the clinical characteristics and survival of 185 patients with hepatitis B virus-related hepatocellular carcinoma (HBV group) and 1033 with hepatitis C virus-related hepatocellular carcinoma (HCV group) by multi center study. The patients in the HBV group (mean age 52.1 yr) were about 10 years younger than those in the HCV group (mean age 62.9 yr). Liver function, as measured by indocyanine green retention at 15 min, was better in the HBV group (17.5%) than in the HCV group (25.4%). A higher propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 10 publications
7
39
0
2
Order By: Relevance
“…In our study, proportion of HCV associated HCC were older in age when comparing it with HBV associated HCC patients with a mean age difference of more than 10 years. The finding from our study is consistent with previous studies, included data from United States of America (Hiotis et al, 2012) and Japan (Tanizaki et al, 1997). One of the sequential reasons behind this difference can be explained by recalling the duration of progression these two diseases takes to develop chronic severe infections, cirrhosis, and hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, proportion of HCV associated HCC were older in age when comparing it with HBV associated HCC patients with a mean age difference of more than 10 years. The finding from our study is consistent with previous studies, included data from United States of America (Hiotis et al, 2012) and Japan (Tanizaki et al, 1997). One of the sequential reasons behind this difference can be explained by recalling the duration of progression these two diseases takes to develop chronic severe infections, cirrhosis, and hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…The overall mean age of the study subjects was 53 years, which was quite similar to 53.8 in the study on HCC cases in northern Thailand (Leerapun et al, 2013). The mean age of the HBV-positive HCC cases were 10 years lower than those with HCV positive (48.0 versus 61.4 years), which was similar to a study in Japan (Tanizaki et al, 1997). A study conducted by the Bellevue Hospital Center in New York also found an 8-year discrepancy (Hiotis et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…La mayor parte de los pacientes tenían entre 60 y 80 años en el momento del diagnóstico y la edad media (68,5 años) fue superior a la observada en Japón (52 años) e Italia (60 años) y similar a la detectada en Estados Unidos (4,8,15). Respecto a los factores etiológicos del CHC, al igual que en otras series, con frecuencia se asoció el abuso de etanol con las hepatitis crónicas de etiología vírica y predominó la infección por el VHC sobre la infección por el VHB, si bien la proporción de casos seropositivos para el VHC (42,8%) fue menor que la hallada en otras zonas de España y en otros países mediterráneos (8,(22)(23)(24).…”
Section: Discussionunclassified
“…Se han descrito diversos factores pronósticos del CHC: un diagnóstico precoz y la posibilidad de tratamiento quirúrgico o ablativo son factores pronósticos positivos, mientras que niveles de alfafetoproteina elevados, la afectación multicéntri-ca y la presencia de trombosis venosa portal se han asociado a una evolución peor (7,14,15). En lo referente a la influencia de la infección por virus hepatotropos en la supervivencia, en un grupo de pacientes con CHC que recibieron tratamiento quirúrgico, Ahmad et al (16) detectaron una menor supervivencia libre de enfermedad en aquellos que presentaban infección por el VHC o por el VHB.…”
Section: Introductionunclassified